Advanced method of scintillator energy resolution test - Gektin, A.V.; Suzdal, V.S.; Boyarintsev, A.Yu.; Sobolev, A.V. (Functional Materials, 2019)
This work is devoted to the development of advanced method of scintillator energy resolution test. Separation of scintillation photons for different groups in accordance with statistical methods allows to extract some groups of photons that give better resolution values comparing to conventional approach. It is shown that new method could be useful for analysis of scintillation uniformity of detector.